Information technology of higher education monitoring: a quality-based approach - Cherednichenko, Olga; Riabko, Olha (Технологический Центр, 2011)
The principles of information technology development for the system of higher education monitoring are considered. For education quality estimation the evidence model is built. It consists of scoring models based on stakeholders’ preferences and measurement model which is implemented using the modern measurement theory.

Розглянуто принципи розробки інформаційної технології моніторинга системи вищої освіти. Побудована модель оцінювання якості освіти, що складається з оціночних моделей, основаних на вподобаннях зацікавлених осіб, та вимірювальної моделі, реалізованої засобами сучасної теорії вимірювань.
Keywords: higher education; monitoring; information technology; evidence model; моніторинг системи вищої освіти; інформаційна технологія; модель оцінювання